Comparison on conjunctival sac bacterial flora of the seniors with dry eye in Ganzi autonomous prefecture - Zhang, Yue (International Journal of Ophthalmology Press, 2013)
AIM: To compare the bacterial flora in palpebral conjunctiva of xerophthalmia seniors of Tibetan, Yi and Han, and analyze the differences and similarities of the bacteria. METHODS: The test subjects were selected from 2 Tibetan, 2 Yi and 3 Han populated places, respectively. Total 222 seniors (444 eyes) with dry eye were examined. Secretion was collected from the palpebral conjunctiva of the subjects and then inoculated onto a blood agar plate. After 48h of incubation, the bacteria were examined for the differences and similarities between different ethnics. RESULTS: There was no significant difference (P>0.05) of Gram stain characterization, dominant bacteria and number of the bacterial species present in oxrophthalmia patients among Tibetan, Yi and Han nationalities. The bacteria presented in all groups include staphylococcus epidermidis, corynebacterium, micrococcus luteu, intracellular bacteria sphingomonas, pseudomonas aeruginosa. The bacteria detected from the two of three ethnic groups were staphylococcus aureus, staphylococcus haemolyticus, escherichia coli, kytococcus sedentarius, streptococcus angina, micrococcus lylae, and staphylococcus heads. The incidence rate of bacteria-associated dry eye in Tibetan population was significantly lower than that of Han and Yi population. CONCLUSION: There is no significant difference in the bacteria flora of palpebral conjunctiva observed among dry eye elder populations of Tibetan, Yi and Han people. All of staphylococcus epidermidis, corynebacterium, micrococcus luteu, intracellular bacteria sphingomonas, pseudomonas aeruginosa, staphylococcus aureus, staphylococcus haemolyticus, escherichia coli, kytococcus sedentarius, streptococcus angina, micrococcus lylae and staphylococcus heads are common bacteria flora of the three nationalities inhibiting in this area.